Social Issues Raised In The Works Of Arundhati Roy (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper delves into the impactful literary and activist contributions of Arundhati Roy, a prominent Indian author. Roy's works have garnered international recognition for their profound exploration of social issues within the context of contemporary Indian society. Through a detailed analysis of her novels and essays, this paper aims to unravel the layers of Roy's critique on various socio-political aspects. The primary focus will be on dissecting the thematic elements within her works, specifically addressing socio-economic, political, and cultural challenges. By adopting an interdisciplinary approach, the research endeavors to illuminate how Arundhati Roy's narratives serve as a lens through which we can better comprehend the intricate tapestry of social issues prevailing not only in India but also on a global scale. This exploration seeks to contribute to a nuanced understanding of the profound impact literature can have on societal awareness and discourse.